Upper limb home-based robotic rehabilitation in chronic stroke patients: A pilot study - Bressi, Federica; Campagnola, Benedetta; Cricenti, Laura; Santacaterina, Fabio; Miccinilli, Sandra; Di Pino, Giovanni; Fiori, Francesca; D'Alonzo, Marco; Di Lazzaro, Vincenzo; Ricci, Lorenzo; Capone, Fioravante; Pacilli, Alessandra; et al. (Frontiers in Neurorobotics, 2023)
Robotic therapy allow to propose sessions of controlled and identical exercises, customizing settings and characteristics on the individual patient. The effectiveness of robotic assisted therapy is still under study and the use of robots in clinical practice is still limited. Moreover, the possibility of treatment at home allows to reduce the economic costs and time to be borne by the patient and the caregiver and is a valid tool during periods of pandemic such as covid. The aim of this study is to assess whether a robotic home-based treatment rehabilitation using the iCONE robotic device has effects on a stroke population, despite the chronic condition of patients involved and the absence of a therapist next to the patient while performing the exercises. All patients underwent an initial (T0) and final (T1) assessment with the iCONE robotic device and clinical scales. After T0evaluation, the robot was delivered to the patient’s home for 10 days of at-home treatment (5 days a week for 2 weeks) Comparison between T0 and T1 evaluations revealed some significant improvements in robot-evaluated indices such as Independence and Size for the Circle Drawing exercise and Movement Duration for Point-to-Point exercise, but also in the MAS of the elbow. From the analysis of the acceptability questionnaire, a general appreciation of the robot emerged: patients spontaneously asked for the addition of further sessions and to continue therapy. Telerehabilitation of patients suffering from a chronic stroke is an area that is still little explored. From our experience, this is one of the first studies to carry out a telerehabilitation with these characteristics. The use of robots can become a method to reduce the rehabilitation health costs, to ensure continuity of care and to arrive in more distant places or where the availability of resources is limited. From the data obtained, this rehabilitation seems to be promising for this population. Moreover, promoting the recovery of the upper limb, iCONE can improve patient’s quality of life. It would be interesting to conduct RCT studies to compare a conventional treatment in structure with a robotic telematics treatment.